2019
DOI: 10.3390/en12091791
|View full text |Cite
|
Sign up to set email alerts
|

A Method to Monitor IGBT Module Bond Wire Failure Using On-State Voltage Separation Strategy

Abstract: On-state voltage is an important thermal parameter for insulated gate bipolar transistor (IGBT) modules. It is employed widely to predict failure in IGBT module bond wires. However, due to restrictions in work environments and measurement methods, it is difficult to ensure the measurement accuracy for the on-state voltage under practical working conditions. To address this problem, an on-state voltage separation strategy is proposed for the IGBT modules with respect to the influence of collector current (Ic) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Note that V ce,on depends on the temperature and current, which requires the measurement at the same working point and same temperature. To tackle this problem, [62] decomposes the voltage into three parts and gives the temperature and current dependent formula of each part. In this way, the degradation caused component can be estimated even the temperature or current varies.…”
Section: D: Multiplexer-based Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that V ce,on depends on the temperature and current, which requires the measurement at the same working point and same temperature. To tackle this problem, [62] decomposes the voltage into three parts and gives the temperature and current dependent formula of each part. In this way, the degradation caused component can be estimated even the temperature or current varies.…”
Section: D: Multiplexer-based Methodsmentioning
confidence: 99%
“…V ref 3 is set such that it exceeds the gate voltage supply V D while smaller than the gate voltage under FUL V ge,FUL . A possible value is given in (62). Hence, when the voltage drop across R 2 is higher than V ref 3 , the FUL can be detected.…”
Section: B Short-circuit Fault Detection Methodsmentioning
confidence: 99%
“…When the IGBT module experiences thermal cycling, thermal induced stresses will be produced at both the solder joints within the system and at the interconnection between the silicon chip and the aluminium bond wire. These thermal-mechanical stresses experienced within the IGBT will be responsible for solder-joint fatigue [18] [19] and bond wire lift-off [20] [21], which are the two dominant failure mechanisms experienced within the IGBT module. Information on the number of cycles before either of these failure mechanisms are triggered can be found based on physics of failure model and SCADA data, and as such plays an important role in optimizing the O&M strategy for the power converter of the offshore wind turbine.…”
Section: State-of-the-art Review Summarymentioning
confidence: 99%
“…An inspected IGBT module in a power circuit can be taken as a resistor-inductor-capacitor (RLC) network during switching transitions, where the equivalent RLC network is dependent on the joint conditions of the multilayer structure. It has been reported that collector voltage v ce,on under small current [11][12][13] and low order harmonics of the output voltage [14] are effective DSEPs for RLC degradation detection. However, additional auxiliary and sampling circuits for DSEPs measurement are needed during testing.…”
Section: Introductionmentioning
confidence: 99%